Mecanismos de accountability no cenário competitivo de sistemas escolares - Silva , Prociana Ferreira da (2016)
In the context of a globalized world the democratization of the state has become a central theme in contemporary political theory and its process aims at tackling the structural contradictions that caused the emergence of different conceptions of state reforms, in order to highlight democratic legitimacy. The literature devoted to this theme shows, in its debates, points of disagreements, however, it presents an intersection point that the democratization demand the deepening of accountability, understood as the necessity of the State to account their actions to society by creating mechanisms democratic participation. In this context, the use of the accountability model, as a result of democratic models, also comes to the educational field, because the dispute between countries for competitive place in the global market has led governments to be concerned about the result of their school system and this necessity has been answered by implementing accountability policies. This model has been developed in European countries, North American and in Brazil. The research aims to examine whether the accountability strategies deployed in the network management system of basic education of the Department of Education of Pernambuco State - Brazil - favored mechanisms of democratic management, opportunities for participation and participatory experiences and empowerment. This is an exploratory study, performed through documentary research. The documents were organized according to their peculiar characteristics as political, regulatory and administrative. Data analysis was carried out from categories prepared based on the theoretical framework and through the of content analysis method. The results indicate that the accountability model implemented in the network management system of basic education in Pernambuco consists of evaluation, accountability and reporting, as well as meet the essential elements of accountability processes: information, justification and the sanction. This study has limitations, so we recommend a deepening of the proposed theme, in order to understand the long-term effects of the reform undertaken in the state of Pernambuco.